PENGARUH KEPEMIMPINAN, MOTIVASI DAN LINGKUNGAN KERJA TERHADAP KINERJA KARYAWAN PT PLN (PERSERO) DISTRIBUSI JAWA TENGAH DAN DIY DI KOTA SEMARANG - Agung Giri Kusuma; Wahyu Hidayat; Sendhang Nurseto (Universitas Diponegoro, 2013)
Human resources is one factor that has an important role in improving employee productivity. To increase the productivity performance of the employees need to be posed. Given the important role of human resources, the company must pay attention to the factors that affect employee performance. One is the application of good leadership, so that employees can be persuaded to work according to standard and put aside their personal interests. Motivation will encourage someone to work more work spirit. Work environment will create a sense of comfort in the work so as to increase productivity. This study aimed to determine the effect of the variable of leadership, motivation and work environment on employee performance PT. PLN (Persero) Distribusi Jawa Tengah dan DIY. This type of research is explanatory research. Technique slovin samples formula was used resulted 94 people for sample and the spreading using the method of Probability Sampling (Stratified Random Sampling). Likert scale was used as measurement scale. Simple linear regression test and regression test with SPSS 16.0 program were used in the data analysis. The conclusion of this research is 65.7% of the respondents classified as good leadership, 47.8% of respondents stated motivation is quite good, 76.1% of respondents said the work environment in either category and 52.21% respondents claimed to have good performance. Variable leadership influence on the performance by 19.2%. Motivation variables affect the performance of 56.6%. Environment variables affect the performance of 17.1%. Taken together the leadership, motivation and work environment affect the performance of 76.4%. This means more and better leadership, motivation and work environment are expected to increasingly higher levels of performance. Based on the results of this study led PT. PLN (Persero) Distribusi Jawa Tengah dan DIY could further increase the frequency of meetings to communicate the company's rules and policies, so as to steer employees are clearer and more attention to the conflict in the company. Providing incentives or bonuses should be increased to boost employee morale. Have good working environment should be maintained, because the working environment comfortable and conducive environment will improve employee performance